Corrosive wear and electrochemical corrosion performances of arc sprayed Al coating in 3.5% NaCl solution. Issue 2 (8th March 2021) - Li, Peng; Huang, Xiya; Kong, Dejun
Abstract : Purpose: The purpose of this paper is to investigate the effects of load and speed on the corrosive wear performance of Al coating in 3.5% NaCl solution, which provided an experimental reference for the anti-corrosion engineering on offshore platforms. Design/methodology/approach: A layer of Al coating was prepared on S355 steel using an arc spraying. The corrosive wear test was carried out with CFT–1 type surface property tester. The effects of load and speed on the corrosive wear performance of Al coating were investigated and the wear mechanism was also discussed. The electrochemical tests were conducted using a CHI660E type electrochemical workstation, the anti-corrosion mechanism was analyzed. Findings: The average coefficient of frictions (COFs) of Al coating under loads of 1.5, 2.5 and 3.5 N are 0.745, 0.847 and 0.423, the wear mechanism is abrasive wear. The average COFs of Al coating at the speeds of 200, 400 and 600 rpm are 0.745, 0.878 and 0.617, respectively, the wear mechanism at the speeds of 200 and 400 rpm are abrasive wear, while that at the speed of 600 rpm is abrasive wear and fatigue wear. The anti-corrosion mechanism is the isolation of Cl – corrosion and cathodic protection of sacrificial anode. Originality/value: This paper mainly studied corrosive wear and electrochemical corrosion performances of Al coating. This study hereby confirms that this manuscript is the original work and has not been published nor has it been submitted simultaneously elsewhere. This paper further confirms that all authors have checked the manuscript and have agreed to the submission.